Novel iron compositions and methods of making and using same

By developing aqueous iron sucrose compositions, including iron sucrose and bicarbonate, the unstable iron release and oxidative stress caused by existing iron-carbohydrate complexes at high doses, achieving more effective renal protection Effect.

CN119488480APending Publication Date: 2025-02-21RENIBUS THERAPEUTICS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411305791.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-02-28
Filing Date
2020-02-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When used at high doses, existing iron-carbohydrate complexes are easily caused by unstable iron release, causing oxidative stress and kidney damage.

Method used

An aqueous iron sucrose composition is developed, comprising iron sucrose and bicarbonate, and combined with a pharmaceutically acceptable aqueous carrier, which is superior to the absorption and protective effects of iron sucrose alone in the kidneys.

Benefits of technology

The composition is preferentially absorbed in the kidney, resulting in preferential upregulation of renal protection molecules, enhancing renal protection effects, and can be used in combination with other renal protection agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488480A_ABST
    Figure CN119488480A_ABST
Patent Text Reader

Abstract

The present application relates to novel iron compositions and methods of making and using the same. The present invention relates to a novel aqueous iron composition. The aqueous iron composition comprises iron sucrose and bicarbonate. The aqueous iron compositions of the present invention exhibit enhanced renal protection relative to conventional iron sucrose compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the application date of February 28, 2020, application number "202080031484.X" and invention name "New iron composition and its manufacturing and use method".

[0002] This application claims priority to Provisional Application No. 62 / 812,028, filed on February 28, 2019, entitled Novel Iron Compositions and Methods of Marking and Using the Same, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present application relates to novel iron compositions and methods of making and using the same. Background Art

[0004] Intravenous (IV) iron reagents are colloids made from Figure 1 The composition of the spherical iron-carbohydrate nanoparticles is shown in Figure 1. The core of each particle is an iron-oxyhydroxide gel, and the core is surrounded by a carbohydrate shell that stabilizes the iron-oxyhydroxide (the main function of the ligand is to stabilize the complex and prevent it from further multinuclearization).

[0005] Iron carbohydrate complexes are used as prodrugs because the iron must be released from the iron (III)-hydroxide core. According to the proposed mechanism, after administration, stable (type 1) complexes such as ferric carboxymaltose and ferric dextran are endocytosed by macrophages of the reticuloendothelial system (RES). See Danielson, J., Structure, chemistry, and pharmacokinetics of intravenous iron agents, Am. Soc. Nephrol., 2004, 15, S93-S98.

[0006] In the case of poorly stable iron(III)-carbohydrates (type 2), a large amount of labile iron can be released from the complex and lead to saturation of transferrin and to large amounts of non-transferrin-bound iron (NTBI), especially when high doses are administered. This weakly bound Fe3+ is easily taken up by cells in an unregulated manner and may induce oxidative stress. Evans, RW; Rafique, R.; Zarea, A.; Rapisarda, C.; Cammack, R.; Evans, PJ; Porter, JB; Hider, R.C. Nature of non-transferrin-bound iron: studies oniron citrate complexes and the thalassemic era. J. Biol. Inorg. Chem., 2008, 13, 57-74.

[0007] There are currently five FDA-approved injectable iron-carbohydrate products (1) (Iron dextran), (superparamagnetic nano-iron oxide (ferumoxytol)), (Carboxymaltose iron), (Sucrose Iron), (Sodium iron gluconate complex). The iron sucrose sold is formulated into a colloidal suspension with a molecular weight (M w ) is about 34,000-60,000 Daltons and has the following molecular formula:

[0008] [Na2Fe5O8(OH)·3(H2O)] n m(C 12 H 22 O 11 )

[0009] Where n is the degree of iron polymerization and m is the number of sucrose molecules (C.sub.12H.sub.22O.sub.11) complexed with the polynuclear polymeric iron core:

[0010] [Na2Fe5O8(OH)·3(H2O)] n

[0011] Each mL contains 20 mg of elemental iron in the form of iron sucrose in water for injection. Available in 5 mL single-dose vials (100 mg elemental iron per 5 mL) and 10 mL single-dose vials (200 mg elemental iron per 10 mL). The drug product contains approximately 30% sucrose w / v (300 mg / mL) and has a pH of 10.5-11.1. The product does not contain preservatives. The osmotic pressure of the injection is 1,250 mOsmol / L.

[0012] Methods for synthesizing iron carbohydrates are described by Lawrence et al. in WO 97 / 11711 (1997), which disclose iron oxyhydroxide-dextran compositions for treating iron deficiency having oval particles preferably in the molecular weight range of about 250,000 to 300,000 Daltons.

[0013] Recently, iron sucrose has been used in combination with tin protoporphyrin (SnPP) to induce acquired cellular resistance without causing damage to organs. See U.S. Pat. No. 9,844,563 to Zager et al. The present inventors have found a need for an iron sucrose formulation that can be easily combined with tin protoporphyrin (SnPP), which is stable and can be injected into patients alone or in combination with another agent such as SnPP to treat iron deficiency or achieve its renal protective effect. Summary of the invention

[0014] The present invention relates to aqueous sucrose iron compositions having desirable properties. In one aspect, the aqueous sucrose iron composition comprises sucrose iron and bicarbonate. In one aspect, the present invention relates to an aqueous iron pharmaceutical composition comprising: sucrose iron; bicarbonate; and a pharmaceutically acceptable aqueous carrier. In another aspect, the present invention relates to a method for preventing or treating a kidney disease or condition comprising intravenously administering a therapeutically effective amount of an aqueous iron composition, wherein the aqueous iron composition comprises sucrose iron and bicarbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The structure of an iron carbohydrate is shown.

[0016] Figure 2 is a Western blot of kidneys 18 hours after administration of the aqueous iron composition.

[0017] Figure 3 GPC chromatograms of three S1 preparations are shown.

[0018] Figure 4 Shows Figure 3 Zoomed view of the .

[0019] Figure 5GPC chromatograms of three S1 preparations are shown.

[0020] Figure 6 Shows Figure 5 Zoomed view of the .

[0021] Figure 7 GPC chromatograms of three S1 preparations are shown.

[0022] Figure 8 Shows Figure 7 Zoomed view of the .

[0023] Fig. 9 A GPC comparison of S1, S2 and S3 is shown.

[0024] Fig.10 AFM top and side views of S1 are shown.

[0025] Fig.11 Particle size analysis at S1, position 1, is shown.

[0026] Fig.12 S1 is shown, manual cross-section analysis of three particles.

[0027] Fig.13 FTIR spectra of S1 and the best library match sucrose are shown.

[0028] Fig.14 FTIR spectra of S2 and the best library match sucrose are shown.

[0029] Fig.15 FTIR spectra of S3 and the best library match dextran are shown.

[0030] Fig.16 The 1H NMR spectrum of S1-Formulation 1 is shown.

[0031] Fig.17 The 1H NMR spectrum of S2-Formulation 1 is shown.

[0032] Fig.18 The 1H NMR spectrum of S3-Formulation 1 is shown.

[0033] Fig.19 The 13C NMR spectrum of S1-Formulation 1 is shown.

[0034] Fig. 20 The 13C NMR spectrum of S2-Formulation 1 is shown.

[0035] Fig.21 The 13C NMR spectrum of S3-Formulation 1 is shown.

[0036] Fig. 22A comparison of the raw data of three samples (lyophilized) is shown.

[0037] Fig.23 An offset overlay of data from all three samples (two replicates of S3) is shown.

[0038] Fig.24 TGA thermograms of S1, S2 and S3 under nitrogen purge conditions are shown.

[0039] Fig.25 DSC thermograms of S1, S2 and S3 are shown. DETAILED DESCRIPTION

[0040] In one embodiment, the present invention relates to an aqueous sucrose iron (FeS) and bicarbonate (FeS-bicarbonate) composition. The inventors have found that the present composition has beneficial properties. On the one hand, the FeS-bicarbonate composition of the present invention can be used as a renal protective agent. The inventors have found that, compared with commercially available forms of FeS, the FeS-bicarbonate composition according to an embodiment of the present invention is preferentially absorbed in the kidney. In addition, the inventors have found that, relative to FeS alone, FeS-bicarbonate causes preferential upregulation of renal protective molecules. On the other hand, the FeS-bicarbonate composition of the present invention can be advantageously combined with other renal protective agents such as tin protoporphyrin (SnPP) to easily form an injectable renal protective agent.

[0041] One advantage of using FeS-bicarbonate is that the present composition results in enhanced renal protection. Specifically, the inventors have found that FeS-bicarbonate preferentially upregulates renal protective molecules relative to FeS alone. Although not wishing to be bound by theory, the inventors have proposed that bicarbonates other than FeS may alter the relative levels of Fe(III) and Fe(II) present. Due to the redness observed in FeS-bicarbonate products, the inventors have proposed that the composition of the present invention may include elevated levels of Fe(II). Given the higher reactivity of Fe(II) relative to Fe(III), this may explain the elevated renal protection.

[0042] One advantage of using FeS-bicarbonate is that bicarbonate has a buffering effect. This may be advantageous when using a tin protoporphyrin composition because SnPP is best stored at a low pH to prevent unwanted dimerization during storage. According to the present disclosure, the SnPP composition can be combined with FeS-bicarbonate at a SnPP:FeS ratio of less than or equal to about 1:1, such as about 1:2, about 1:4, about 1:8, about 1:10, about 1:20, about 1:50, about 1:100, about 1:1000, about 1:10,000, about 1:100,000, about 1:1,000,000, or any integer or sub-range therebetween.

[0043] In one aspect, the composition has a molecular weight measured using GPC as described in Example 1. Mp is preferably in the range of between 25,000 and 35,000 daltons, more preferably between 28,000 and 32,000 daltons, and most preferably about 29,000 daltons. Mw is preferably in the range of between 25,000 and 45,000 daltons, more preferably between 30,000 and 40,000 daltons, even more preferably between 33,000 and 38,000 daltons, and most preferably about 34,000 daltons. Mn is preferably in the range of between 15,000 and 30,000 daltons, more preferably between 20,000 and 25,000 daltons, and most preferably about 24,000 daltons. The polydispersity (PDI) is preferably in the range of 1.35 to 1.60, more preferably in the range of 1.38 and 1.5, even more preferably in the range of 1.40 and 1.48, and most preferably about 1.4.

[0044] In one aspect, the composition has a stable zeta potential of -3.0 mV or less, more preferably -7.0 mV or less, and most preferably about -10 mV. In one aspect, the composition has a total organic carbon of less than 8.5%, preferably less than 8.0%, and most preferably about 7.7%. In one aspect, the osmotic pressure measured according to Example 1 is in the range of 550 and 1600 mOsm / kg, preferably in the range of 1500 and 1580 mOsm / kg, and most preferably about 1540 mOsm / kg.

[0045] Example 1

[0046] The present invention relates to a composition prepared by dissolving enough sucrose iron complex in water (about 3.5L) to obtain a 12mg / mL (expressed as iron) solution when diluted to 6.0L. The amount of sucrose iron required for the final volume of the liquid, 6100mL (6.1L), is calculated so that the final concentration is 12mg / mL. This requires 73.2g of iron. The efficacy of sucrose iron is 0.0550. Therefore, 73.2g / 0.0550 or 1331g±1g of sucrose iron is required. 1331g±1g of sucrose iron is weighed directly into a 6.0L conical flask. About 3-3.5L of water is added to the conical flask, and the contents of the flask are stirred.

[0047] The amount of sodium bicarbonate added should be such that the final sodium bicarbonate concentration is 10 mg / mL when diluted to 6.0 L. Weigh 109.8 ± 0.1 g of sodium bicarbonate and add to the 6.0 L flask.

[0048] The amount of sodium chloride added should be such that the final sodium chloride concentration after dilution is 9.0 mg / mL. Weigh 54.9 ± 0.1 g of sodium chloride and add it to a 6.0 L flask. Stir the suspension for 30-120 minutes to obtain a black opaque solution.

[0049] Monitor the pH of the solution with a pH meter while adding 1M sodium hydroxide in small portions until pH 10.30 is reached and remains stable. Add 40.0±0.1g of sodium hydroxide to a 1.0L conical flask. Add 1.0±0.1L of water to a 1.0L conical flask and stir until all the sodium hydroxide is dissolved. Fix a pH probe to monitor the pH of the 6.0L conical flask and add sodium hydroxide in <100mL portions until pH=10.3±0.1. Then, stir the solution for 10 minutes. Check the pH again after 10 minutes and adjust it to within pH=10.3±0.1 if necessary.

[0050] Then, transfer the solution to a precise volume flask and dilute with water to 6.1 L. Use a 2L volumetric flask to accurately transfer 4L of the 10.3 pH solution to a 6L conical flask twice. The remaining 10.3 pH solution was diluted to 2L in a volumetric flask and added to a 6L conical flask. Use a 100mL graduated cylinder to add 100 ± 0.1mL to a 6.0L conical flask, and stir the resulting solution for 10 minutes.

[0051] The resulting product solution was dark red to brown. Two iron isotopes were present in the sample preparation in a ratio consistent with that in the standard preparation. The resulting material had a pH of 10.3, which is within the preferred limit of 10.1-10.4. The resulting material had 11.5 / 11.6 parts per thousand (mg / mL) iron according to SOP 174472 for determination of iron by inductively coupled plasma mass spectrometry.

[0052] Further properties of the resulting composition can be found in Table 1 below:

[0053]

[0054]

[0055] The resulting FeS-bicarbonate composition has the following stoichiometry and physical constants, as shown in Table 2 below:

[0056]

[0057]

[0058] Example 2

[0059] The intravenous administration of the iron sucrose (FeS) bicarbonate salt composition of Example 1 was carried out for 4 hours and resulted in a decrease in the amount of iron sucrose (FeS) bicarbonate salt compared to the composition sold under the trade name The commercially available sucrose iron (FeS) composition was sold to increase renal heme oxygenase 1 (HO-1). The results are shown in Table 3 below.

[0060]

[0061] The increase in HO-1 levels observed in the kidney was not observed in the liver. Conversely, no increase in HO-1 levels was observed with FeS-bicarbonate relative to The results are shown in Table 4 below.

[0062]

[0063] FeS, Plasma BUN and creatinine were similar for FeS-bicarbonate as shown in Tables 5 and 6 below.

[0064]

[0065]

[0066]

[0067] Example 3

[0068] The FeS-bicarbonate composition of Example 1 was filtered and placed in a vial and had a FeS concentration of 12 mg / mL (CoreRx Lot No. 111002-18011). The osmotic pressure of this 12 mg / mL solution was 831 mOsm. Iron Sucrose Injection 20 mg / mL, American Regent, Lot No. 8243A, osmolality is 1742 mOsm. These osmolality measurements were performed without dilution.

[0069] Example 4

[0070] Western blot of kidneys 18 hours after administration of aqueous iron composition Figure 2 And as shown in Table 7:

[0071] Table 7

[0072] kidney normal Venofer RBT3 HO-1mRNA 0.1±0.04 1.59±0.21 2.34±0.23 <0.001 <0.001(<0.05) Ftn LC mRNA 1.10±0.06 1.36±0.04 1.47±0.09 <0.01 <0.02(NS) Ftn HC mRNA 1.38±0.01 1.38±0.03 1.49±0.06 NS NS(<0.05)*

[0073] liver normal Venofer RBT3 HO-1mRNA 0.10±0.01 0.97±0.012 0.64±0.12 <0.001 <0.01(0.085) Ftn LC mRNA 3.65±0.15 4.02±0.1 3.63±0.13 NS NS Ftn HC mRNA 1.77±0.11 1.82±0.1 1.71±0.14 NS NS

[0074] Left is a heavy chain specific Western blot of kidneys 18 hours after SnPP, FeS (Venofer) or Fe+SnPP. N = normal control. Glyc is glycerol, used as a positive H chain ferritin control. N = normal sample (control). Clearly, Fe induces an increase in heavy chains in the kidney.

[0075] Example 5

[0076] Patients with chronic kidney disease were treated intravenously using the aqueous iron composition of iron sucrose and bicarbonate of Example 1.

[0077] Example 6

[0078] Patients undergoing organ transplantation were treated intravenously using the aqueous iron composition of iron sucrose and bicarbonate of Example 1.

[0079] Example 7

[0080] Patients undergoing organ transplantation were treated intravenously using the aqueous iron composition of iron sucrose and bicarbonate of Example 1 in combination with tin protoporphyrin.

[0081] Example 8

[0082] Three samples of iron-sucrose (S1, S2) and iron-dextran (SB) were characterized by various analytical techniques. S1 was prepared according to Example 1 above. S2 is a commercially available product (Iron Sucrose Injection). S3 is a commercially available product (Iron Dextran Injection). The results are summarized in Table 8 below.

[0083]

[0084]

[0085]

[0086]

[0087] Finally, the received sample S1 was titrated with dilute HCl in triplicate to determine the hydroxyl value of the iron-sucrose injectable solution. The endpoint of the titration was pH = 7.0. Assuming that all the basic species titrated were from the hydroxide associated with the iron oxyhydroxide core, the H + The total number of moles is equal to OH - Taking into account TOC and Mw (or Mn) obtained by GPC, the molecular formula of ferric sucrose in S1 is calculated as follows:

[0088] Calculation based on Mw: [Na6Fe5O8(OH)5·3H2O]13·73(C12H22O11)

[0089] Calculation based on Mn: [Na6Fe5O8(OH)5·3H2O]9·51(C12H22O11). Details of sample preparation and identification are shown in Table 9 below.

[0090]

[0091]

[0092] Sample preparation:

[0093] Unless otherwise stated, samples were lyophilized to dry residues prior to analysis.

[0094] Gel Permeation Chromatography (GPC):

[0095] GPC is used to determine the molecular weight distribution of polymers. In GPC analysis, a polymer solution is passed through a column filled with a porous gel. The sample is separated based on molecular size, with larger molecules eluting faster than smaller molecules. The retention time of each component is measured and compared to a calibration curve, and the resulting data is then used to calculate the molecular weight distribution of the sample.

[0096] It is not the molecular weight that is unique, but the molecular weight distribution that is characteristic of all types of synthetic polymers. To characterize this distribution, statistical averages are used. The most common of these averages are the "number average molecular weight" (Mn) and the "weight average molecular weight" (Mw).

[0097] The number average molecular weight is similar to the standard arithmetic mean associated with a set of numbers. When applied to polymers, the number average molecular weight refers to the average molecular weight of the molecules in the polymer. The number average molecular weight is calculated so that each molecule has the same importance regardless of its individual molecular weight. The number average molecular weight is calculated by the following formula, where Ni is the number of molecules with a molar mass equal to Mi.

[0098]

[0099] The weight average molecular weight, Mw, is calculated slightly differently and has a very different meaning. The weight average molecular weight is another statistical descriptor of the molecular weight distribution that gives greater importance to larger molecules than to small molecules in the distribution. The following formula shows the statistical calculation of the weight average molecular weight.

[0100]

[0101] For GPC, samples were prepared by dilution in phosphate buffer (as per USP monograph method) and analyzed to determine the molecular weight distribution in each sample. The results are summarized below in Tables 10-12. Representative chromatograms from the analysis are given in Figure 3-9 Presented in.

[0102] There are two general reasons for weight average molecular weight. First, if you compare, for example, toughness, longer molecules have a greater impact on the toughness of a polymer distribution than shorter molecules. The weight average molecular weight calculation emphasizes these longer molecules and provides a comparative number that can describe the relative contribution of long molecules present in a molecular weight distribution. The weight average molecular weight is also a number that is directly related to polymer molecular weight determinations by light scattering, small angle neutron scattering (SANS), and sedimentation velocity.

[0103] Second, the weight average molecular weight provides insight into the shape of the molecular weight distribution. This value, along with the number average molecular weight, provides a ratio determination of the breadth of the molecular weight distribution, which is called the polydispersity index or PI. The PI is defined as the ratio of Mw / Mn. The larger the PI, the more dispersed the distribution. The lowest possible value for PI is 1. This represents a monodisperse sample - a polymer in which all molecules in the distribution have the same molecular weight.

[0104] Although not usually mentioned, a "z-average molecular weight" (Mz) is also provided. This molecular weight average is a value that further describes the molecular weight distribution. This value can be easily determined from sedimentation equilibrium.

[0105] Sometimes the peak molecular weight Mp is also included. The peak molecular weight value is defined as the mode of the molecular weight distribution. It represents the most abundant molecular weight in the distribution. This value also provides insight into the molecular weight distribution.

[0106] Most GPC measurements are made relative to different polymer standards (usually polystyrene). The accuracy of the results depends on how well the properties of the polymer being analyzed match those of the standards used. The expected reproducibility error between different series of measurements that are calibrated separately is about 5-10% and is a characteristic of the limited precision of GPC measurements. Therefore, GPC results are most useful when comparing the molecular weight distributions of different samples during the same series of measurements.

[0107] GPC precision and bias are based on statistical data, such as the measurement mean, standard deviation, relative percentage difference and / or relative standard deviation percentage. For quantitative analysis, the amounts listed in the table above are referenced to standards of known quantity and are quantitative. A calibration curve was prepared, and the relative standard deviation and relative percentage difference information were referenced in the above report. For semi-quantitative, the typical reproducibility determined by statistical process control of the measurement system is estimated to be about 10% (95% confidence level, k~2). This reproducibility is an estimate of the uncertainty of a single standard measurement over time, and the uncertainty in a specific measurement must be determined on a case-by-case basis. For qualitative analysis, the analytical reference standards were not analyzed to confirm the presence of individual components. In this case, it is not possible to assign a numerical value to the "uncertainty" of the provided match.

[0108] Note that samples S1 and S2 contain two peaks with unique molecular weight distributions, while sample SB contains three peaks. Note also that the Mp for "Peak 2" (the small molecule peak, probably sucrose) could not be calculated because the peak saturated the detector; the samples were analyzed at concentrations appropriate for characterizing higher molecular weight species at the expense of saturating the detector with lower molecular weight species of less interest.

[0109]

[0110]

[0111]

[0112]

[0113]

[0114] Dynamic Light Scattering

[0115] PSD analysis is performed using a laser diffractometer. The measurement calculates the volume distribution based on the laser diffraction spectrum of the particle cloud. This raw scattering data is then processed using an algorithm and presented based on the equivalent sphere diameter. The results have been summarized in a bar graph based on volume (mass), giving the differential volume percentages below and above the indicated size.

[0116] Particle size analysis in The scattering data is processed using a complex algorithm and presented based on the intensity-weighted hydrodynamic diameter (HYDRODYNAMIC DIAMETER). The analytical techniques are summarized in ISO 22412:2008 Particle Size Analysis-Dynamic Light Scattering (DLS) and ASTM E2490-09 (2015) Standard Guide for Measurement of Particle Size Distribution of Nanomaterials in Suspension by Photon Correlation Spectroscopy (PCS) for the measurement of particle size distribution of nanomaterials in suspension by photon correlation spectroscopy (PCS).

[0117] The samples were received as water for injection (WFI) and were analyzed by DLS to give the bulk physical size of the particles.

[0118] The intensity-weighted and volume-weighted results from the analysis are presented in Tables 13 and 14, respectively.

[0119]

[0120]

[0121] 1NNLS = non-negative least squares data; 2 Z-mean = average particle size distribution; 3 PDI = Polydispersity Index

[0122]

[0123]

[0124] 1NNLS = non-negative least squares data; 2 Z-mean = average particle size distribution; 3 PDI = Polydispersity Index

[0125] Zeta potential

[0126] The samples were prepared by diluting in buffer to obtain the zeta potential (according to Nanomaterials 2018, 8, 25, the instrument could not obtain a stable reading when diluted in 10 mM NaCl). pH and temperature were recorded during the zeta potential analysis. The results are summarized in Tables 6 to 8 below. A stable reading of S2 could not be obtained. The results of the zeta potential test are given in

[0127] Reported in Tables 15-17.

[0128]

[0129]

[0130]

[0131]

[0132] Atomic Force Microscopy (AFM)

[0133] The received samples were diluted 50 times using MilliQ filtered water (18.2 MΩ / cm, 4 ppb TOC). Approximately 10 μL of these diluted solutions were deposited onto freshly cut mica sheets and allowed to incubate for approximately 1 minute. The samples were then rinsed 5 times with MilliQ water and dried with nitrogen. Two 1 μm x 1 μm areas were imaged on each sample. The topographic differences in these images are presented in brown as low and white as high colors. The z range is annotated on the vertical scale bar on the right side of the image. Perspective (3-D) views of these surfaces are also included with the vertical exaggerations noted in the title.

[0134] Particle size analysis was performed to characterize the height of the particles present in each region. A height threshold of 0.5 nm was used to identify particles of interest while excluding non-representative features. The maximum height, minimum height, and average height results are summarized in Table 18.

[0135]

[0136] Cross-section analysis was performed to manually measure the height of a representative particle. Cross-section analysis of S1 at position 1 was performed at Fig.10 , 11 and 12. For each of S1, S2, SB, the results are summarized in Table 19.

[0137]

[0138] Total Organic Carbon (TOC)

[0139] The total organic carbon (TOC) in the sample was calculated by subtracting the inorganic carbon from the total carbon (determined using a combustion carbon analyzer).

[0140] The results are summarized in Table 20 below.

[0141]

[0142] 1wt% = weight percentage; 2 %RSD = relative standard deviation

[0143] Osmotic pressure

[0144] The osmotic pressure of the samples was measured using the vapor pressure method. The vapor pressure method determines the osmotic pressure of the sample when it is naturally in equilibrium at room temperature. The results of the osmotic pressure test are summarized in Table 21.

[0145]

[0146] Fe +3 with Fe +2

[0147] An aliquot of each sample was diluted into concentrated hydrochloric acid according to the method reference provided by the client Gupta et al.1 The samples were then analyzed according to the method outlined by Stookey.2 The results are shown in Table 22.

[0148]

[0149] %RSD = relative standard deviation

[0150] Elemental screening by inductively coupled plasma / mass spectrometry (ICP / MS) and total iron and sodium content by inductively coupled plasma / optical emission spectrometry (ICP / OES)

[0151] ICP / OES is a spectroscopic technique used to identify and quantify components by element. In ICP, inductive coupling transfers high-frequency energy into an inert gas stream that contains the sample in the form of an aerosol. The energy vaporizes the aerosol while exciting the resulting free atoms, causing them to emit light. The intensity of this light is then related to the concentration of the emitting atoms. This technique requires calibration of the instrument and second source calibration verification before, during, and after the completion of a sequence of analytical runs. In addition, an instrument blank follows each check verification standard. This ensures that there is no carryover during the analytical sequence. The uncertainty of concentration measurements of major elements made by ICP is typically in the range of 3% to 5% (95% confidence level). The uncertainty in the concentration of trace elements can be much higher.

[0152] Samples S1 to S3 were analyzed by ICP-MS for metals and / or other elements. The samples were also analyzed by ICP-OES to determine total iron and sodium content. The samples were analyzed as received in triplicate. The results are summarized in Tables 23-25.

[0153]

[0154]

[0155]

[0156]

[0157]

[0158]

[0159]

[0160]

[0161]

[0162]

[0163]

[0164]

[0165] Fourier Transform Infrared Spectroscopy (FT-IR)

[0166] Fourier transform infrared spectroscopy (FT-IR) is the tool of choice for identifying materials. In FT-IR, infrared absorption bands are assigned to characteristic functional groups. Based on the presence of multiple such bands, the material under consideration can be identified. The availability of spectra of known compounds increases the likelihood of making a positive identification. The freeze-dried samples were analyzed by horizontal attenuated total reflectance (HATR) based on internal reflection of infrared radiation (IR). The FT-IR spectrum of S1 with a spectral library match is given below Fig.13 The data show that the material is consistent with sucrose. The FT-IR spectra of S2 and S3 are Fig.14 and Fig.15 The distribution of absorbance to functional groups is shown in Tables 26 to 28.

[0167]

[0168]

[0169]

[0170]

[0171] 1H Nuclear Magnetic Resonance Spectroscopy (NMR)

[0172] Nuclear magnetic resonance spectroscopy is a very useful method for the characterization of materials. NMR is a physical phenomenon based on the magnetic properties of atomic nuclei. NMR studies magnetic nuclei (most commonly the nuclei of hydrogen atoms) by aligning them with a very strong external magnetic field and perturbing this alignment using electromagnetic pulses. The response to the perturbation is recorded, with each individual nucleus giving a response specific to its chemical, electronic and spatial environment.

[0173] Lyophilized samples were reconstituted in deuterium oxide (D2O) and analyzed by 1H NMR spectroscopy.

[0174]

[0175] The structure of sucrose is shown above with hydrogen annotations of formula (I). The 1H NMR of S1 is shown below in Table 29:

[0176]

[0177]

[0178]

[0179] The structure of dextran is shown above with hydrogen annotations of formula (II). Table 30 below shows the 1H NMR of S3.

[0180]

[0181] The NMR spectra of the prepared samples were Figure 16-18 Where possible, preliminary assignments of the main chemical shifts observed in the NMR spectra were based on reference spectra of related compounds available in the literature.

[0182] The data indicated the presence of sucrose in sample S1 and the chemical shifts matched closely those reported in the literature. However, no peak splitting was observed, which could be due to a variety of reasons, such as the presence of nanoparticles or the paramagnetic iron itself.

[0183] The 1H NMR spectrum of sample S2 exhibits a large amount of peak broadening. It is unclear whether this is due to the particles causing an increased number of chemical environments, or whether the nature of the iron in the sample may result in insufficient resolution. Due to the extent of broadening, peak assignments could not be made. However, the general peak intensities and chemical shifts are consistent with those observed for sucrose, as a large broad response is observed from chemical shifts 2.5-4.2 ppm, with a slight shoulder visible on the solvent peak near 5.5 ppm.

[0184] 13C Nuclear Magnetic Resonance Spectroscopy (NMR)

[0185] Lyophilized samples were reconstituted in deuterium oxide (D2O) and analyzed by 13C NMR spectroscopy.

[0186] The results are summarized in Tables 28-30. The NMR spectra of the prepared samples were Figure 19-21 Where possible, preliminary assignments of the main chemical shifts observed in the NMR spectra were based on reference spectra of related compounds available in the literature.

[0187] The data indicates the presence of sucrose in samples S1 and S2, and the chemical shifts closely match those reported in the literature. Note that, as with the proton spectrum, sample S2 appears to be more broadened than sample S1. Finally, the peak observed in sample SB closely matches the literature values ​​for dextran, indicating its presence in the sample.

[0188]

[0189] The structure of sucrose is shown above with carbon annotations. The results of 13C NMR are shown in Table 31 below:

[0190]

[0191]

[0192]

[0193] The structure of dextran is shown above with carbon notation of formula (III). Table 33 below shows the 13C NMR of dextran of S3 in D2O:

[0194]

[0195] X-ray diffraction (XRD) analysis (freeze-dried material)

[0196] XRD analysis is a method of irradiating a crystalline inorganic sample with monoenergetic X-rays. The interaction of the sample's lattice structure with these X-rays is recorded, and it provides information about the irradiated crystalline structure. The resulting characteristic "fingerprint" allows the identification of the crystalline compounds present in the sample. Using full spectrum fitting analysis (Rietveld Refinement), samples containing more than one crystalline compound can be quantitatively analyzed.

[0197] The freeze-dried samples were analyzed by XRD to characterize the chemical structures and phases present in the samples. The results from the analysis are presented in Table 34. Note that this sample preparation method resulted in particularly viscous samples for S1 and S2 (S3 was less viscous). For S1 and S2, a drop of methanol was added to the sample and the material was then spread flat into the sample holder. Sample S3 was ground in a mortar and pestle.

[0198]

[0199] For clarity, Fig. 22 The XRD raw data from three samples are superimposed with a small offset. Sample S2 differs from the other two samples in overall intensity, peak position, and peak shape. The broad peak shape in samples S1 and S3 indicates that these samples consist of a mixture of nanocrystalline and amorphous materials.

[0200] Using the best match obtained by comparing the background modeling experimental data with the ICDD / ICSD diffraction database for samples S1, S2 and S3, respectively, it was determined that samples S1 and S3 contained a mixture of amorphous and nanocrystalline materials. The sodium iron oxide reference spectrum was superimposed on these experimental data. The markers indicate the location of the expected diffraction peaks for each phase, and the marker height indicates the relative peak intensity of the fine-grained randomly oriented material. Unlike the other two samples, sample S3 is mainly composed of sucrose and amorphous materials.

[0201] Semi-quantitative analysis was performed using WPF (Whole Spectrum Fitting), a subset of Rydberg refinement that accounts for all areas above the background curve. This technique requires that the structure factors and atomic positions or reference intensity ratios (a way to compare the diffraction capabilities of different phases) of all identified phases are known. During this process, the structure factor (related to concentration), lattice parameters (related to peak position), peak width and peak shape are refined for each phase to minimize the R value - an estimate of the agreement between the model and experimental data over the entire spectrum.

[0202] In order to obtain quantitative results from samples that contain measurable amounts of amorphous material, the density of the amorphous material must be specified to determine how much amorphous material is present. Therefore, the concentration of amorphous material is uncertain. It is assumed that the location of the amorphous peak in these samples is from amorphous sucrose, which has a density of approximately 1.59 g / cm3. Since WPF attempts to account for everything in the sample, any error in the amorphous concentration will also result in an error in the crystalline phase. This means that the relative concentration of the crystalline phase is accurate, but the absolute value will be wrong by an amount proportional to the error in the amorphous concentration.

[0203] X-ray diffraction (XRD) analysis (sugar-free materials)

[0204] The received sample was diluted in water and placed in a 10000Da molecular weight cutoff (MWCO) filter and centrifuged to remove small molecules (sugars) in the formulation, which would result in amorphous material in the previous XRD analysis. The sample was then washed five more times with water to remove residual small molecules. The resulting material (able to pass through the filter) was freeze-dried and analyzed by XRD to characterize the chemical structure and phases present in the sample. Note that sample S3 contained two different layers after centrifugation, a thick viscous layer and a thinner top layer. These layers were separated and freeze-dried separately and analyzed as two samples. The results were averaged to provide the values ​​seen in Table 35, but the individual replicates for each layer are presented in the figure below. The results from the analysis are presented in Table 35.

[0205]

[0206]

[0207] wt% = weight percentage ± 5%; average of 2 replicate formulations (two layers observed)

[0208] Fig.23 The superposition of XRD spectra from all four samples (two repetitions of S3) is shown in . For the sake of clarity, the spectrum is offset. Phase identification is performed by comparing the best match between the background modeling experimental XRD data and the ICDD / ICSD diffraction database of the sample. If the sample is fine-grained and randomly oriented, the reference mark of the phase shows which position the expected experimental peak represented by 2θ should be located at, and the height of the mark indicates the expected intensity of the experimental peak. Note that XRD is sensitive to crystal structure, but is relatively insensitive to element or chemical state composition. Due to the nanocrystalline nature of the sample significantly broadens the peak in the XRD spectrum, it is difficult to phase identify these samples.

[0209] The peaks present in all four samples most closely match the iron oxide and hydroxide phases known as maghemite. The hydroxide phase is atypical in that it is formed by heating the beta phase of oxyhydroxide to approximately 300°C. Unfortunately, this reference card does not contain the reference intensity ratios (RIRs) required for semi-quantitative analysis. However, due to its similar symmetry and composition to the oxyhydroxide mineral goethite (α-FeOOH), the average RIR of goethite was used for semi-quantitative analysis of the oxyhydroxide.

[0210] Semi-quantitative analysis was performed using WPF (Whole Spectrum Fitting), a subset of Rydberg refinement that accounts for all intensities above the background curve. This technique requires that the structure factors and atomic positions or reference intensity ratios (a way to compare the diffraction capabilities of different phases) of all identified phases are known. During this process, structure factors (related to concentration), lattice parameters (related to peak position), peak widths, and peak shapes are refined for each phase to minimize the R value - an estimate of the agreement between the model and experimental data over the entire spectrum.

[0211] Acid Degradation of Labile Iron(III) Using UV-Vis Spectroscopy

[0212] UV / Vis spectroscopy is used to determine the concentration of an analyte once or frequently over a desired period of time. The technique measures the light absorption of ultraviolet and visible wavelengths by a liquid sample. The sample is dispensed into vials and placed between the UV / Vis light path and the detector. According to the Beer-Lambert law, the concentration of the compound can be determined based on the light absorbed by the sample at that wavelength, given a constant light path length and a known absorption coefficient that depends on the wavelength.

[0213] The samples were analyzed using a method adapted from BS Barot et al. (2014) which used UV-visible spectroscopy to determine the amount of labile iron (III) in the samples. The results are summarized in Table 36 below.

[0214]

[0215] Thermogravimetric analysis (TGA)

[0216] TGA consists of measuring the weight change of a material as the temperature changes in a controlled atmosphere. The technique requires accurate measurements of weight, temperature, and temperature change. From the resulting thermogram generated by the analysis, the content of component categories (e.g., solvents, polymers, inorganic fillers, etc.) and the thermal stability of the polymer can be determined. The typical accuracy and deviation of TGA measurements are discussed under ASTM E2040.

[0217] The freeze-dried samples were analyzed by thermogravimetric analysis (TGA) under nitrogen purge and air purge. The thermal decomposition of the samples occurred in three different steps, such as Fig.24 The results of these steps are summarized in Table 37.

[0218]

[0219]

[0220] Differential Scanning Calorimetry (DSC) and Differential Thermal Analysis (DTA)

[0221] Lyophilized samples were analyzed by differential scanning calorimetry (DSC) under argon purge. Differential scanning calorimetry (DSC) measures the difference in heat flow associated with the transition between a sample and an inert reference as a function of temperature and time. Such measurements provide quantitative and qualitative information about physical and chemical changes involving endothermic or exothermic processes or changes in heat capacity. DSC thermograms are available at Fig.25 A summary of the DTA is presented in Table 38 below.

[0222]

[0223] n / a = not observed; 2* possible overlapping transitions

[0224] Hydroxyl number obtained by titration and determination of molecular formula

[0225] As-received sample S1 was titrated in triplicate with 0.00998N HCl to determine the hydroxyl value in the iron-sucrose injectable solution. The endpoint of the titration was pH = 7.0. Table 39 summarizes the results of this titration in S1.

[0226] Assuming that all basic species titrated are from the hydroxide associated with the iron oxyhydroxide core, the total number of moles of H+ used in the titration is assumed to be equal to the number of moles of OH-. Taking into account the TOC and the Mw obtained by GPC, the molecular formula of the iron sucrose in S1 is calculated as follows:

[0227] [Na6Fe5O8(OH)5·3H2O]13·73(C12H22O11)

[0228] If Mn is considered in this calculation, the molecular formula is:

[0229] [Na6Fe5O8(OH)5·3H2O]9·51(C12H22O11)

[0230]

[0231] By considering the specification and practice of the invention disclosed herein, other embodiments and uses of the present invention will be apparent to those skilled in the art. All references cited herein, including all U.S. and foreign patents and patent applications, are hereby specifically and fully incorporated herein by reference. The specification and examples are intended to be considered exemplary only, with the true scope and spirit of the present invention being indicated by the following claims.

Claims

1. An aqueous iron composition comprising: Sucrose iron; and Bicarbonate.

2. An aqueous iron composition according to claim 1, wherein the composition has a pH greater than 9.

3. An aqueous iron composition according to any one of the preceding claims, wherein the composition has a pH in the range of about 10.5 to about 11.

5.

4. An aqueous iron composition according to claim 1 or 2, wherein the composition has a specific gravity at 20°C between 1.135 and 1.

165.

5. An aqueous iron composition according to claim 1 or 2, wherein the composition has a Mw according to GPC between 30,000 and 40,000 Daltons.

6. An aqueous iron composition according to claim 1 or 2, wherein the composition has a Mw according to GPC between 33,000 and 38,000 Daltons.

7. An aqueous iron composition according to claim 1 or 2, wherein the composition has a maximum iron (II) concentration of 0.40% w / v.

8. An aqueous iron composition according to claim 1 or 2, wherein the composition has an iron (II) concentration of 0.05% w / v to 0.40% w / v.

9. An aqueous iron composition according to claim 1 or 2, wherein the composition has an iron (II) concentration of 0.10% w / v to 0.20% w / v.

10. Use of a therapeutically effective amount of an aqueous iron composition in the manufacture of a medicament for preventing or treating a kidney disease or condition, wherein the aqueous iron composition comprises iron sucrose and bicarbonate.

Citation Information

Patent Citations

  • Compositions, kits, and methods to induce acquired cytoresistance using stress protein inducers

    US9844563B2

  • Iron dextran formulations

    WO1997011711A1